Մամիկոնյանների տիրույթների խնդիրը VIII դ. վերջին - Խաչատրյան, Հենրիկ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Начиная с 700–885 гг. Армения вместе со странами Южного Кавказа (Картли, Арран, Ширван и Дербент) представляла собой единую административную единицу Арминия Арабского халифата. Мамиконяны были одним из сильных, если не сильнейшим нахарарским (княжеским) родом, который владел обширными землями. Уже с VII в. видно соперничество между Мамиконянами и нахарарами Багратуни. В VIII в. институт Первенствующего князя (Князь Армении), кроме двух случаев, в основном находился в руках князей Багратуни. Во второй половине VIII в. Мамиконяны, а точнее их ветвь из Тарона во главе с Мушегом Мамиконяном приобрели крепость Артагерс с сопредельными землями, которая находилась в уезде Аршаруник. После поражения в битве с арабами при Ардзни в 775 г. Мамиконяны на время покинули политическую арену Армении. Хотя они ослабли, так как вложили в битву весь свой военный потенциал, но не исчезли, как нахарарские роды Камсараканов, Хорхоруни, Рштуни и т д. После битвы участники восстания из рода Багратуни покинули свои владения чтобы избежать мести арабов. Точка зрения, что Ашот Мсакер Багратуни завладел доменами ослабших Мамиконянов уже вскоре после 775 г., не обоснована. Ашот Мсакер в начале IX в., когда стал Князем Армении, перенес свою резиденцию из уезда Коговит в уезд Аршаруник, часть которого он купил у потомков ослабших Камсараканов. Это опирается на сообщение историка Асогика. Уже после этого Ашот Мсакер как Первенствующий князь начал расширять свои феодальные владения. Вместе со своим братом Шапухом завоевал у араба Джахапа другую часть уезда Аршаруник, который принадлежал Мамиконянам, потому что он был женат на дочери Мушега Мамиконяна и сам планировал завоевать Аршаруник полностью. После этого, они взяли уезд Ширак, Ашоцк и провинцию Тайк. По косвенным сведениям Вардана вардапета можно предположить, что Ашот Мсакер, будучи по материнской линии потомком рода Мамиконянов, мог претендовать на Тайк. Что в конечном счете и случилось: он завоевал Тайк, затем и уезд Тарон. Нельзя точно утверждать, сохранили ли Мамиконяны все свои территории в VIII в. Можно только уверенно сказать, что в начале IX в. они потеряли Тайк и Тарон, в итоге сохранив только уезд Багреванд и часть Сасун-Хута. Beginning from the year of 700 to the middle of the 9th century, Armenia together with the countries of the South Caucasus (Kartli, Arran, Shirvan and Derbent) constituted a single administrative unit called Arminiya of Arab Caliphate. The Mamikonyans were one of the strong, if not the strongest Nakharar (princely) family, which owned vast lands. Already from the 7th century the rivalry between the Mamikonyans and the Nakharars of Bagratuni is visible. In the 8th century, the institution of the First Prince (Prince of Armenia), except for two cases, was mainly in the hands of the princes of Bagratuni. In the second half of the 8th century the Mamikonyans, or rather their branch from Taron, led by Mushegh Mamikonyan, acquired the Artagers fortress with adjacent lands, which was located in the Arsharunik district. After the defeat in the anti-Arab battle of Ardzni in 775, the Mamikonyans became so weak that they temporarily left the political arena of Armenia. Although they weakened, as they had put all their military potential in that battle, they did not disappear like the Nakharar clans of the Kamsarakans, Khorkhorunis, Rshtunis, etc. After the battle, participants in the uprising from the Bagratuni clan left their possessions to avoid the revenge of the Arabs. The point of view that Ashot Msaker Bagratuni took possession of the domains of the weakened Mamikonyans shortly after 775 is not supported. At the beginning of the 9th century Ashot Msaker, when he became the Prince of Armenia, moved the residence of the Prince from Kogovit to the Arsharunik district, part of which he had bought from the descendants of the weakened Kamsarakans. This is based on Asoghik's report. After this, as the Prince of Armenia, he began to expand his feudal holdings. Together with his brother Shapuh, he conquered, from the Arab Jahapp, the other part of the Arsharunik district, which belonged to the Mamikonyans, as he was married to the daughter of Mushegh Mamikonyan and he planned to conquer Arsharunik completely. After that, they took the district of Shirak, Ashotsk and the province of Tayk. According to the indirect information from Vardan Vardapet, one can assume that Ashot Msaker, being a descendant of the Mamikonyan clan on his mother’s side, could lay claim to Tayk, which ultimately happened. He conquered Tayk, then the district of Taron. We have no information on whether the Mamikonyans retained all their territories in the 8th century. We can confidently say that at the beginning of the 9th century they lost Tayk, then Taron, eventually retaining only the district of Bagrevand and part of Sasun-Khut.
Keywords: Պատմություն